Educação inclusiva no ensino fundamental: desafios e possibilidades - Gonçales, Valdineia de Fatima Roventini (Universidade Federal de São Carlos, 2025)
This paper addresses the topic of Inclusive Education in Elementary School, highlighting the challenges and possibilities for developing pedagogical practices that respect diversity and ensure the right to learning for all students. Based on a literature review, the study seeks to understand the foundations of school inclusion and reflect on the role of the school, teachers, and the school community in the inclusion process. The article presents concepts, legislation, and proposals for inclusive actions, focusing on ensuring meaningful learning for students with disabilities, pervasive developmental disorders, and giftedness/high abilities. It is based on the premise that Inclusive Education is a fundamental principle for building a democratic and equitable society. In the context of Elementary Education, the inclusion of students who are the target audience of Special Education poses challenges to educational institutions and professionals, requiring didactic, pedagogical, and structural adaptations.
Inclusive education in elementary school: challenges and possibilities
Keywords: Educação inclusiva; Ensino fundamental; Diversidade; Prática pedagógica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM